CDKN2A Mutation Analysis, Protein Expression, and Deletion Mapping of Chromosome 9p in Conventional Clear-Cell Renal Carcinomas : Evidence for a Second Tumor Suppressor Gene Proximal to CDKN2A - Schraml, Peter (American Society for Investigative Pathology, 2001)
Inactivation of tumor suppressor genes on chromosome 9p is considered a critical event in renal cell carcinoma pathogenesis. Alterations of CDKN2A on 9p21 have been reported in renal cancer cell lines, but their relevance for primary renal carcinomas is unclear. Loss of heterozygosity (LOH) was analyzed by using four polymorphic microsatellites at D9S970 (9p12-9p13), D9S171 (9p13), D9S1748 (9p21), and D9S156 (9p21) in 113 primary conventional clear-cell renal cell carcinomas (CRCCs). Allelic deletion was detected in 21 of 88 informative CRCCs (24%) with the highest rate of LOH being observed at D9S171 on 9p13 (20%). Chromosome 9p LOH was associated with short tumor-specific survival in stage pT3 RCC (P = 0.01). Fluorescence in situ hybridization analysis of 54 CRCCs revealed no homozygous CDKN2A deletions indicating that this mechanism of CDKN2A inactivation is rare in CRCC. Sequencing of 113 CRCCs showed that 13 tumors (12%) had a 24-bp deletion abrogating codons 4 through 11 of CDKN2A. Immunohistochemical CDKN2A expression was absent in normal renal tissue and was only detected in six of 382 CRCCs (1.5%) on a renal tumor microarray. These data suggest that CDKN2A alterations are present in a small subset of CRCCs and a second, yet unknown tumor suppressor gene proximal to the CDKN2A locus, may play a role in CRCC development.